Pentingnya Gizi dan Pengelolaan Stres dalam Menjaga Kesehatan Reproduksi Remaja Putri: Upaya Pencegahan Polimenorea - Sherkia Ichtiarsi Prakasiwi; Aric Vranada (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Polymenorrhea is a menstrual cycle disorder characterized by an interval of less than 21 days, indicating an imbalance in reproductive hormones among adolescent girls. This condition not only causes physical discomfort such as fatigue, abdominal pain, and excessive bleeding but also affects psychological well-being, leading to stress, anxiety, and decreased learning concentration. One of the major contributing factors to polymenorrhea in adolescents is nutritional imbalance combined with poor stress management skills. Preliminary observations revealed that adolescent girls in RW 01, Mangunharjo Village, experienced a high prevalence of polymenorrhea, low knowledge of balanced nutrition, and high levels of academic and social stress. This community service program aims to improve adolescents’ knowledge and skills regarding reproductive health, balanced nutrition, and stress management as preventive measures against menstrual cycle disorders. The activities were conducted through interactive education sessions, personal mentoring, and regular monitoring of behavioral changes and menstrual patterns. The educational approach emphasized active participation and direct application in daily life. It is expected that this structured intervention will enhance adolescents’ awareness and adoption of healthy lifestyle behaviors, reduce the incidence of polymenorrhea, and promote sustainable physical and mental well-being. Furthermore, the outcomes of this program are expected to serve as a model for empowering adolescents to maintain reproductive health through simple, non-pharmacological, and community-based approaches.